Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Is this 11x-6y=-4, 9x-7y=-3?

If so:

11x=6y-4, x=(6y-4)/11,

9(6y-4)/11-7y=-3,

9(6y-4)-77y=-33,

54y-36-77y=-33,

-23y=3, y=-3/23, 

x=(6y-4)/11=(-18/23-4)/11=-(18+92)/(23×11)=-110/253=-10/23.

So x=-10/23 and y=-3/23.

This solution seems to indicate a mistake in the question.

If you meant 11x-6y=-4, 9x-7y=3, then:

Substituting x=(6y-4)/11 into 9x-7y=3:

9(6y-4)/11-7y=3,

54y-36-77y=33,

-23y=69, y=-69/23=-3.

x=(6y-4)/11=-22/11=-2.

So x=-2 and y=-3. This is a more likely solution.

Can also be solved:

11x-6y=-4

9x-7y=3

77x-42y=-28 (multiplying 1st equation by 7)

54x-42y=18 (multiplying 2nd equation by 6)

Subtract:

23x=-46, x=-2, so substituting for x in either equation:

-22-6y=-4, -18=6y, y=-3, and -18-7y=3, -7y=21, y=-3.

by Top Rated User (825k points)

Related questions

1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
86,149 questions
92,144 answers
2,246 comments
23,903 users